On multivalent starlike functions and Ozaki condition - Nunokawa, Mamoru; Sokół, Janusz (Complex variables and elliptic equations, 2019)
We prove some new sufficient conditions for function to be p-valent, or p-valently starlike in the unit disc. We extend in some sense the Ozaki condition which says that if for some real , then is at most p-valent in a convex domain .